KEPENTINGAN INDIA MENOLAK PERMOHONAAN HAK PATEN OBAT KANKER DARI PERUSAHAAN NOVARTIS NEGARA SWISS - Yuyun Syaputri; Den Yelta (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
The purpose of this research are to explain about the Interest from India applying the protection's policy to the Pharmacy Industrial of India. The type of protection by putting article 3(d) in 2005's amandement as a reference.This research is an international economic politic study. This research using merchantilisme perspective, in this perspective state as a main actor which actively and rational organize the economy to increase the power of State. Analysis's step that have been using in this research is Nation-State. This research also using protectionism theory that explain how is Nation's effort to protect national interest, focus on International economy.Pharmacy Industrial could growing in fast as a produsen of biggest generic medicine in the world. The submisson of cancer medicine licensed (Glivec) that makes India worry. Because of that India try to protect the pharmacy by using Article 3(d) amandement laws 2005.Keywords : Patents. Pharmacy Industrial, India, Novartis, Pritectionism